Measuring Investment Fund Health Against Total Asset Growth in Islamic Insurance Companies in Indonesia - Ramadhani Irma Tripalupi; Siti Asma’ Binti Mohd Rosdi (IAIN Syekh Nurjati Cirebon, 2025)
The mechanism of fund management in sharia insurance includes fund distribution allocation, namely tabarru' (donation) funds and saving funds, which are integral parts in carrying out sharia insurance management. Regulation No. 11/PMK.010/2011 concerning the finncial health of Sharia insurance companies outlines of the health of Sharia insurance companies includes two things, namely the financial health of tabarru' funds and company funds, with distinct solvency limits for each. The solvency limit for tabarru’ funds is 30%, while for company funds, it is 70%. The purpose of this study is to examine the impact of the allocation of Islamic insurance fund assets, including mudharabah (profit-sharing) deposits, government sukuk (Islamic bonds), corporate sukuk, and Islamic mutual funds, on the asset growth of Islamic insurance funds in Indonesia. This study used quantitative methodology by utilizing Vector Autoregression (VAR) and Ordinary Least Squares (OLS) to analyze a data series covering the period from January 2017 to April 2025. The findings of the ordinary least squares (OLS) analysis indicated that the proportion of funds invested in Islamic mutual funds, government sukuk, corporate sukuk, and mudharabah deposits has a substantial and positive impact on the growth of Islamic insurance assets. In addition, the findings from VAR indicated that a positive and statistically significant short-term relationship exists exclusively with government sukuk and its impact on the growth of Islamic insurance assets. To optimize the allocation of investment funds for investors and stakeholders, government and corporate sukuk are viable considerations, supported by impulse response function and variance decomposition analyses.